2014
DOI: 10.1080/07399332.2014.900060
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Community WithPromotores de Saludto Support Infant Nutrition and Breastfeeding Among Latinas Residing in Los Angeles County:Salud con Hyland's

Abstract: The Salud con Hyland's Project: Comienzo Saludable, Familia Sana [Health With Hyland's Project: Healthy Start, Healthy Family],was developed to provide education and support to Latina mothers regarding healthy infant feeding practices and maternal health. The promotora-delivered intervention was comprised of two charlas (educational sessions) and a supplemental, culturally and linguistically relevant infant feeding and care rolling calendar. Results indicate that the intervention increased intention to breastf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 37 publications
(43 reference statements)
1
27
0
Order By: Relevance
“…Mirroring findings from research conducted with other ethnic groups [ 43 , 83 , 84 , 85 , 86 , 87 , 94 ], findings from studies included in this review showed that early introduction of solids is a common practice [ 54 , 56 , 57 , 60 , 61 ], and that cultural beliefs might influence this practice [ 57 , 60 , 61 ]. Furthermore, a few of reviewed studies showed that some mothers were not knowledgeable about the long-term benefits of breastfeeding, which may result in the early introduction of solids [ 54 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Mirroring findings from research conducted with other ethnic groups [ 43 , 83 , 84 , 85 , 86 , 87 , 94 ], findings from studies included in this review showed that early introduction of solids is a common practice [ 54 , 56 , 57 , 60 , 61 ], and that cultural beliefs might influence this practice [ 57 , 60 , 61 ]. Furthermore, a few of reviewed studies showed that some mothers were not knowledgeable about the long-term benefits of breastfeeding, which may result in the early introduction of solids [ 54 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 87%
“…Maternal infant feeding practices are influential on infant’ and child’s growth, and could possibly explain obesity rates across generations [ 30 , 33 , 39 , 83 ]. A small, but increasing body of research conducted primarily in Western countries, has examined infant feeding practices of ethnic minority immigrant mothers [ 84 , 85 , 86 , 87 ], but limited attention has been paid to Chinese immigrant mothers, a large and growing group in several countries. Therefore, the purpose of this integrative review was to identify and synthesize information from studies examining infant feeding practices conducted among Chinese immigrant mothers in order to describe and highlight factors influencing infant feeding practices of this immigrant group that may be used to inform the design of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…CHWs connected participants to needed services even when not a stated objective of the intervention. For example, within a breastfeeding intervention for Latina mothers, participants reported an increased understanding of where to get help for post-partum depression because the CHW shared her knowledge of relevant services (38).…”
Section: Moore Et Al (36)mentioning
confidence: 99%
“…These women may be most in jeopardy of developing the health disparities affecting this population. Community-based participatory methods, which include building strong relationships with communities, empowering communities to determine their own areas of need, and establishing priorities for health concerns, have demonstrated success with underserved Latina women in the US for issues such as HIV/AIDS (e.g., Rhodes et al, 2012), nutrition (e.g., Wieland et al, 2012), cancer screening (e.g., Larkey et al, 2012), maternal health (Rios-Ellis, Nguyen-Rodriguez, Espinoza, Galvez, & Garcia-Vega, 2015), and access to high-quality health care (Moreno, Rodríguez, Lopez, Bholat, & Dowling, 2009). We also suggest potential novel skill building areas (e.g., offering employment assistance through resume workshops and job skill building) to inform these interventions.…”
Section: Discussionmentioning
confidence: 99%